Mentoring program to eradicate malnutrition on changes in the nutritional status of stunting toddlers - Prihartanti, Niken Grah; Lestari, Rini Hayu; Probowati, Ririn (Trigin Institute, 2023)
Improving nutritional knowledge can be done with the right media without computer equipment into games that are easy, useful and fun are the most important keys in designing game. This type of research is a quasi-experimental research. The sample in this study were 14 stunting toddlers living in Denanyar Village. The research subjects were children aged 6 – 58 months with a Z score of Weight/Age -3 to 0 SD. Variables observed included changes in nutritional status. Data analysis was carried out using different tests and multivariate analysis with linear regression of dummy variables. After 3 months of intervention, the decrease in nutritional status in the intervention group was lower than the control (p<0.05), there was an increase in the Z score Weight/Length score in the intervention group and a decrease in the Z score Weight/Length in the intervention group. Length in the control group (p<0.05). The mentoring model is more effective than conventional counseling in suppressing the decline in the nutritional status of children aged 6-58 months. It is hoped that the Berakzi group mentoring program can be implemented in a sustainable manner and the target area is expanded so that it can reduce the prevalence of stunting in Jombang Regency.